Optimal local foods procurement in the National School Lunch Program: an analysis of potential impacts of Farm to School policies on procurement practices in three northern Colorado school districts - Long, Abigail B., author; Jablonski, Becca, advisor; Costanigro, Marco, advisor; Cunningham-Sabo, Leslie, committee member (Colorado State University. Libraries, 2019)
The most recent Farm to School (FTS) Census reported 23.6 million students in 42,587 schools (representing 42% of surveyed school districts) participated in FTS, with 77% of schools participating by procuring food locally (FNS 2014b). FTS connects K-12 students and local farms in an effort to increase the availability of healthy, local foods in school cafeterias, improve student nutrition, provide health and nutrition education opportunities, and increase market opportunities for small and medium-sized farms. Participation in FTS has been accompanied by legislative support at both the State and Federal levels. Specifically, in Spring of 2019 Colorado joined five other States and the District of Columbia in passing legislation that provides financial incentives for local food procurement (CO HB 19-1132). However, there is little research that assesses the relationship between FTS procurement and typical school food procurement practices carried out by Food Service Managers (FSMs), or quantifies how procurement policies effect procurement decisions by FSMs. This paper utilizes a unique primary data set to assess the role FTS local food procurement plays in optimal school food procurement and how policies incentivizing local procurement may impact purchasing decisions. To conduct this study, we aggregated and analyzed primary data describing real purchasing decisions made by FSMs in three Northern Colorado school districts and use the data to parameterize a Linear Programming (LP) optimization model. The optimization model acts as a proxy to examine a portion of FSM decision making regarding FFV purchasing and was then used to simulate how state reimbursements for local food purchases, as described in CO HB 19-1132, may alter FSMs procurement decision-making. We find that increases in local purchasing associated with reimbursements are nominal at lower reimbursements rates of 1% to 15% of local food purchasing, with substantial increases in local food purchasing and cost savings at higher reimbursement rates of 50% and 100%. When compared to reimbursements provided by CO HB 19-1132 and adjusted for waste we estimate that 20-40% of purchasing of FFV for use on salad bars could be reimbursed in the three districts observed if all reimbursement funds are spent on salad bar FFV exclusively. While promising, our results point to the need for more research that compares cost reductions experienced by schools to overall policy costs to the state, and benefits captured by local farmers.